The Urgency of Heutagogy-Based Local Wisdom in Elementary School Curriculum in Bali - Trisna, Gusti Ayu Putu Sukma; Wahyudin, Dinn; Rusman, Rusman; Riyana, Cepi; Monika, Ketut Ayu Lola (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aimed to analyze the urgency of heutagogy-based local wisdom values in the elementary school curriculum in Bali. This research method used a survey with a qualitative approach. The research was conducted on elementary school teachers in Buleleng Regency, Bali using a purposive sampling technique consisting of 27 elementary school teachers from nine districts. The research instrument was a questionnaire, which consisted of a 2013 curriculum implementation questionnaire, Balinese local wisdom values applied in elementary schools, and teachers' opinions about the importance of heutagogy elements applied to the 2013 curriculum. Data analysis techniques in this study used quantitative and qualitative descriptive analysis. The results of this study indicated that local wisdom is low in the 2013 curriculum, Balinese local wisdom was rarely inserted into learning, and the primary need for 4C elements found in heutagogy. Therefore, character values, actions, works and traditional games of Balinese local wisdom based on heutagogy in the elementary school curriculum were very urgent to be implemented in elementary schools in Bali. Steps that can be taken Â include elaborating the values of local Balinese wisdom in teaching materials, media, evaluation tools, lesson plans, and student worksheets.